Novelty Experience in Prolonged Interaction: A Qualitative Study of Socially-Isolated College Students’ In-Home Use of a Robot Companion Animal - Abendschein, Bryan; Edwards, Autumn; Edwards, Chad (Frontiers in Robotics and AI, 2022)
Social distancing policies such as limits on public gatherings and contact with others were utilized around the world to slow the spread of COVID-19. Yet, decreased social interactions may also threaten people’s well-being. In this project, we sought to understand novelty-relevant experiences surrounding in-home companion robot pets for adults that were living in some degree of social isolation due to the COVID-19 pandemic. After six-weeks of participants living with the robot companion, we conducted semi-structured interviews (N=9) and six themes emerged from our iterative analysis (expectations versus reality, ontological comparisons, interactions, third-party influence, identity, and comfort). Findings suggest that novelty is a complex phenomenon consisting of various elements (i.e., imagined novelty, technology novelty, and relational novelty). Each component influences the user’s experience. Our findings also suggest that our understanding of novelty as a nonlinear resource may hold important implications for how we view human-robot relationships beyond initial encounters.